THE The Relationship of Protein Energy Intake and Infection Diseases with Stunting in Selatan Golewa Subdistrict, Ngada Regency, East Nusa Tenggara Province - Maria Elsa Wea; Lewi Jutomo; Daniela L.Adelin Boeky (Lontar : Journal of Community Health, 2023)
Stunting is a form of body size nutritional disorder characterized by a short body under conditions that exceed a-2 SD deficit under World Health Organization (WHO) criteria. Based on the results of field information in the Laja Health Center, 92 stunting children and 32 malnourished children were distributed over seven villages. This study aims to determine the relationship between energy and protein, intake, and infectious diseases with the incidence of stunting in the work area of the Laja Health Center, Golewa Selatan Subdistrict, Ngada Regency, East Nusa Tenggara Province. This study is an analytical survey research using a case-control design. The number of research samples (32 cases and 32 controls) was selected using a simple random sampling method. The analysis used univariate and bivariate using the chi-square test. The result shows a significant relationship between energy intake and incidence of stunting (OR=8,700: 95%CI=2,493-30,364: p=0,001): infection diseases with the incidence of stunting (OR=4,241: 95%CI=1,479-12,165: p=0,012). The analysis showed no significant relationship between protein intake and the incidence of stunting (OR=3,640:95%CI=1,118-11,894;(p=0,053). It is recommended that mothers of toddlers understand the importance of consuming foods that contain sources of energy and protein, and mothers of toddlers are expected to pay attention to the health of their children.